PERBEDAAN STRATEGI KOPING PADA PEREMPUAN HINDU BALI YANG BEKERJA DAN YANG TIDAK BEKERJA - Angligan, I G. A. Intan Kinanti; Suarya, Luh Made Karisma Sukmayanti (Jurnal Psikologi Udayana, 2016)
In general, women have two roles in life, there are domestic roles  and public roles. In terms of Balinese culture, women have three roles or triple roles in life,  which are reproductive roles, productive roles, and social roles.  Being  Balinese Hindu  women which is inseparable from the customary of traditional bonds, of course, requires a balance in  running are three roles or triple roles in life. There are still many Balinese women imprisoned in a state of dilemma to do a job search for a career, while on the other hand must be a housewife and social activities that unwittingly has its own demands. If this condition is not communicated properly, it can interfere with the psychological condition or stress. To deal with stress and to prevent the negative effects of stress continues to occur, then the individual conduct coping strategies. However, coping strategies do vary considerably between one individual with another individual. This study aims to determine differences in coping strategies in Bali Hindu woman who works and what does not work. This research is a quantitative study using chi-square analysis techniques. The sampling technique used is purposive sampling, on the subject of Balinese Hindu women who worked (being employee) as many as 100 people and who are not working (unemployee) as many as 100 people who live in Denpasar with an age range of 20 years to 40 years. A parametric in this study using a scale of coping strategies as much as 31 item with reliability coefficient of 0,917. The results of this study obtained significance value of 0,406 or is above 0,05 (p>0,05). Based on these results it can be said that there is no difference in coping strategies in employee and unemployee Balinese Hindu woman ( who works and what does not work). A total of 164 subjects in this study belongs to the category of subjects who have combine coping strategies.   Keywords: Balinese Hindu Women, Being Employee, Being Unemployee, Coping Strategies